Impact of Patient Age on Morbidity and Survival Following Laparoscopic Pancreaticoduodenectomy. Issue 5 (October 2019) - Meng, Lingwei; Xia, Qinghong; Cai, Yunqiang; Wang, Xin; Li, Yongbin; Cai, He; Peng, Bing
Abstract : Purposes: To present preliminary perioperative and long-term outcomes in elderly patients compared with younger patients who underwent laparoscopic pancreaticoduodenectomy (LPD). Materials and Methods: A total of 199 patients who underwent LPD were included in this study. The primary data relating to these patients were collected and analyzed in our center from October 2010 to 2017. Results: The intraoperative and postoperative information, including the rate and severity of short-term complications, pathologic outcomes, and other surgical outcomes, showed no significant differences between the 2 groups. Furthermore, the median overall survival for 2 malignant diseases of the young patients was not significantly better than the elderly. Conclusions: Our data suggest that patient age showed little influence on postoperative morbidity, mortality, and long-term survival in pancreatic adenocarcinoma and periampullary adenocarcinoma following LPD, whereas studies with larger sample sizes and longer follow-up are necessary before definitive conclusions can be made.